The influence of a humectant‐rich mixture on normalz skin barrier function and on once‐ and twice‐daily treatment of foot xerosis. A prospective, randomized, evaluator–blind, bilateral and untreated‐control study. Issue 4 (22nd March 2013) - Lodén, Marie; von, Johan; Michelson, Sophie
<x xml:space="preserve">Abstract</x> Background Moisturizers are often used to overcome dry skin conditions. However, cosmetic moisturizers may lack in efficiency and may also deteriorate skin barrier function. The objective of this study was to generate data on a new humectant‐rich formulation (15% alfahydroxy acids and 15% urea) in the treatment of normal skin as well as in dry feet with hyperkeratosis and cracked skin with fissures. Changes in permeability and effectiveness of the product after once‐ and twice‐daily applications to the feet will be monitored. Methods The study was randomized, bilateral, controlled and evaluator‐blind. The first part of the study included 12 healthy volunteers and the second part 50 patients with hyperkeratotic feet. The changes in the skin was evaluated by an expert, the patients and using non‐invasive biophysical measurements of skin barrier function (transepidermal water loss, TEWL), erythema, thickness (ultrasound) and hydration (conductance). Results The humectant‐rich formulation increased skin hydration, removed scales and reduced thickness of hyperkeratotic skin. Skin barrier function was improved in normal skin, but no changes in TEWL were noted in the feet. No difference between once and twice‐daily applications was found. Some smarting and stinging was noted. Conclusion The humectant‐rich formulation efficiently relieved the xerosis on the feet without inducing any weakening of the skin barrier function. Instead the normal skin became more resistant to external insults by the treatment.